Preschoolers’ Moderate-to-Vigorous Physical Activity Measured by a Tri-Axial Accelerometer: Compliance with International Guidelines and Different Cut-Points - Aristides M. Machado-Rodrigues; Thales P. Rodrigues da Silva; Larissa L. Mendes; António Stabelini Neto; Helena Nogueira; Daniela Rodrigues; Cristina Padez (Children)
Background/Objectives: This study aimed to investigate the effect of the most frequently used accelerometer CoPs on the quantification of active preschoolers by weekday; and to analyze children’s physical activity (PA) quantification using a vertical axis and vector magnitude (VM). Methods: A cross-sectional sample of 134 children (70 males) aged 3–5 years was studied. Height, body weight, and BMI were assessed. A tri-axial accelerometer was used for seven consecutive days of MVPA and sedentary behavior (SB). Data were analyzed using the three most used CoPs for active preschooler classification (Johansson, Butte, and Pate). A general linear model with repeated measures examined differences in PA and SB, and the agreements of all CoPs were analyzed using the Kappa index. Results: The CoPs adopted by Pate had the highest percentage of children classified as active for the weekdays (73.9%) and weekend (85.6%). The Johansson CoP classified all children as inactive. Furthermore, the prevalence of active boys was significantly higher than their female counterparts based on the Pate and Butte CoPs for the week and weekends. Conclusions: The lowest prevalence rates of active children were observed at the weekend based on all accelerometer CoPs, especially among girls. The choice of cut-points significantly affects the times calculated for different movement intensities.